1983 as a systemic boundary. Democracy as a contingency formula for the political system in Argentina - Kaipl, Esteban; Rinaldi, Mariano (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2024)
It is not realistic to think that politics is a field able to generate definitive solutions in theoretical terms, and “final” responses as public and binding policies to any popular demand. Societies evolve, so do constitutional States governed by the rule of law. Democracy must be thought as a political form that has to deal with an inexhaustible source of demands. A formal democratic process has begun in 1983 in Argentina. This process contains elements that will put democracy in question or in crisis, but it is perhaps those same elements that give the democratic system greater legitimacy. In other words, what seems to control it is what keeps it alive deeply. The construction of democracy seems to be a contingency formula for a political system that never ceases to close in on itself. The political system cannot be the exact theoretical equivalent of the democratic form, because democracy itself becomes the key that reopens that system again and again. This fact allows to distance ourselves from authoritarian regimes despite the authoritarian deviations of some democratically elected governments.